The relationships of elite sailors’ functional movement screen scores and some of their motoric features with lower extremity pain - Gönener, Utku; Sertbaş, Kürsad; Gönener, Ahmet (Progress in Nutrition, 2020)
Study Objectives: This study aimed to investigate the relationships of elite sailors’ functional movement screening scores (FMS) and some of their motoric features with lower extremity pains. Method: The study included n=23 participants aged between 15-17 years. Functional movement screening, handgrip strength test, vertical jump test, sit-and-reach flexibility test, 1 RM bench press test, 1 RM squat test, and back strength dynamometer test were applied 3 times in pre-season, mid-season, and post-season. In addition to these tests, pains and injuries experienced sufficiently enough to prevent the athletes from training any day during the season were recorded every week from the beginning to the end of the season in accordance with the statements of the athletes. Results: A statistically significant and negative correlation was found between the number and severity of pains experienced in the 17th and 18th regions and the pre-test, mid-test, and post-test FMS scores (p0.05). Likelihood ratios and R2 indices revealed that the 17th region was closer to the significance limit, but the FMS scores had no effect on the number and severity of pains. Conclusion: When FMS scores and regional pain were examined separately, statistically significant and negative relationships were found between the FMS scores and the number and severity of pains in the 17th and 18th regions. The results of the regression analysis showed that the effects of the FMS scores and some motoric features on lower extremity pain were not statistically significant (p>0.05).